THE EFFECT OF SERVICE DELIVERY AUTOMATION (SDA) ON THE SOUTH AFRICAN BANKING INDUSTRY - Akilimalissiga, Save; Sukdeo, Nita (The South African Journal of Industrial Engineering, 2024)
Adoption of automation has become the norm in the South African banking industry, owing to competition. Conventional banking institutions are uncertain of the possible adverse effects of integrating automation into banking processes to serve more customers with fewer resources. This study sought to investigate and model the extent to which the integration of automation could be the exogenous factor of the nine endogenous factors identified in this study. The five most prominent banking institutions in South Africa, were used as a case study. The study used a quantitative approach, and 223 bank employees were selected to contribute to the questionnaire survey, and the primary data were analysed using the structural equation modelling (SEM) technique to test the proposed hypotheses. The secondary information was extracted from the banks’ annual integrated reports and fact sheets to generate additional insights into the primary data findings. The findings revealed that service delivery automation is a significant and direct predictor of productivity, efficiency, flexibility, operations costs, and the generation of new job opportunities (positive effects). Similarly, the adoption of bank automation was found to be significantly related to the generation of job losses, the changing nature of work, unbalanced demand for required skills, and inequality in wages of employees, which are described as adverse effects.